The effects of corruption on foreign direct investment inflows: Some empirical evidence from less developed countries - Azam, Muhammad; Ahmad, Siti Aznor (AENSI Publisher, 2013)
This study investigates the effect of corruption on incoming Foreign Direct Investment (FDI) in a set of 33 Less Developed Countries (LDCs) over the period; 1985 to 2011.Using panel data approach, this study reveals that the significant factors influencing FDI inflows in LDCs are corruption index, market size and inflation rate. Results are in line with the hypotheses of the study. Multinational corporations (MNCs) tend to avoid countries with high corruption rates, which in turn, ineluctably, reduces incoming FDI. The findings suggest that lesser foreign investments receiving countries need to create a better conducive environment for MNCs by concentrating on some of the significant factors identified by the present study. In the same vein, increased and sustainable efforts geared towards mitigating corruption at all levels in the countries, must be put in place to encourage FDI inflows.